THE USE OF ARTIFICIAL INTELLIGENCE TECHNOLOGY IN POLITICAL DIGITAL MARKETING STRATEGIES - Sandra Alfiani; Sri Hastjarjo; Sudarmo Sudarmo (Institut Agama Islam Negeri (IAIN) Ponorogo, 2023)
This research aims to explore the latest developments in the use of Artificial Intelligence in political digital marketing strategies. The current advancement in AI technology offers digital solutions for effective and efficient marketing. Furthermore, the use of AI in political marketing needs to consider factors such as public trust and transparency. The research method employed in this study is a Literature Review, involving data collection through sourcing and reconstruction from various sources, such as books, journals, and existing research. The findings indicate that in the context of digital political marketing, AI is utilized to analyze voter behavior, create emotional connections between candidates/parties and the public, identify potential trends, develop effective campaign strategies, and target specific campaign messages. Some effective AI assistants in supporting political marketing include Cambridge Analytica, Chat GPT, GPT-3, Generative Adversarial Networks (GANs), Brandwatch, and MidJourney. However, challenges in implementing AI in digital political marketing include privacy concerns. Therefore, transparency, ethics, and data security should be prioritized to maintain public trust and protect the integrity of democracy when implementing Artificial Intelligence in political marketing.